Pembuatan Aplikasi Management Keuangan Pribadi Berbasis Android - Bryan Anu Syarwan; Kristo Radion Purba; Alexander Setiawan (Jurnal Infra, 2018)
Finance is something that is very difficult to manage. Most people often feel stressed because they can’t manage their finances well. This resulted in a person's money can be drained out even without realizing it. Often manual recording is difficult because records can be lost forgot to record the transaction.Based on the background of the problem, a Personal Finance Management application based on Android is designed. This application has features such as input income and expenditure, reminder of debt maturity and accounts receivable, bill upload expenditure, backup and restore data, budget to limit expenditure, import data into csv form , as well as transaction reports.The results of this application indicated that 70% of users considered that the application has a complete feature, 80% of users considered the application easy to use, and 70% of users considered the application has a good design.